2020
DOI: 10.1126/sciadv.aay1057
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IRF5 cellular activity with cell-penetrating peptides that target homodimerization

Abstract: The transcription factor interferon regulatory factor 5 (IRF5) plays essential roles in pathogen-induced immunity downstream of Toll-, nucleotide-binding oligomerization domain–, and retinoic acid–inducible gene I–like receptors and is an autoimmune susceptibility gene. Normally, inactive in the cytoplasm, upon stimulation, IRF5 undergoes posttranslational modification(s), homodimerization, and nuclear translocation, where dimers mediate proinflammatory gene transcription. Here, we report the rational design o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 70 publications
1
20
0
Order By: Relevance
“…Last, given the heterogeneity of SLE and the differential kinetics and cell-type specificity of IRF5 activation in NZB/W F1 and MRL/lpr mice, it is unlikely that there is a single trigger or pathway leading to IRF5 activation. Indeed, we recently reported that the kinetics of Ser462 IRF5 phosphorylation and nuclear translocation were distinct depending on the stimulus (39). Unfortunately, this phospho-antibody does not detect endog-disease and contributed to increased survival; significant reductions in proteinuria occurred at 30 weeks (Figure 7, C-G, and Supplemental Figure 10A).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Last, given the heterogeneity of SLE and the differential kinetics and cell-type specificity of IRF5 activation in NZB/W F1 and MRL/lpr mice, it is unlikely that there is a single trigger or pathway leading to IRF5 activation. Indeed, we recently reported that the kinetics of Ser462 IRF5 phosphorylation and nuclear translocation were distinct depending on the stimulus (39). Unfortunately, this phospho-antibody does not detect endog-disease and contributed to increased survival; significant reductions in proteinuria occurred at 30 weeks (Figure 7, C-G, and Supplemental Figure 10A).…”
Section: Discussionmentioning
confidence: 95%
“…Identification of IRF5 as a global risk factor for autoimmune and inflammatory diseases (5,11,20,(36)(37)(38), coupled with its increased activation in the blood of patients with SLE, indicates that IRF5 is an attractive target for therapeutic inhibition. While C-terminal phosphorylation and dimerization represent steps amenable to inhibition (39), neither has been definitively shown to be an absolute requirement for nuclear translocation (35). An alternate approach to inhibiting IRF5 stems from the finding that either N-or C-terminal regions of IRFs can act as dominant-negative (DN) mutants to block transactivation ability (2,29,(40)(41)(42)(43)(44).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to fostamatinib, also other drugs that target key molecules in FcγR signaling could be efficacious to counteract anti-Spike IgG-induced inflammation in COVID-19 patients. For example, the Sykdependent FcγR signaling pathway critically depends on the transcription factor IRF5 (15,28), which can be targeted using cell penetrating peptides (40). Furthermore, FcγR stimulation is known to induce metabolic reprogramming of human macrophages (28), which is also observed in COVID-19 patients (41), and therefore may provide additional targets for therapy.…”
Section: Main Textmentioning
confidence: 99%